Does Infrastructure Reform Work for the Poor? A Case Study from Guatemala - Foster, Vivien; Caridad Araujo, Maria (World Bank, Washington, DC, 2013)
Following the 1996 Peace Accords, Guatemala embarked on a major program of infrastructure reform involving the restructuring and privatization of the electricity and telecommunications sectors and a substantial increase in infrastructure investments partially financed by privatization proceeds. As a result, the pace of new connections to electricity, water, and sanitation services increased by more than 40 percent. Moreover, households in traditionally excluded sectors-the poor, rural, and indigenous populations-were twice as likely to be the beneficiaries of a new infrastructure connection than they had been prior to the Peace Accords. The teledensity index increased by a factor of five from 4.2 in 1997 to 19.7 in 2001, largely because of the growth in cellular telephones, which now outnumber fixed lines. The number of public telephones in rural areas increased by 80 percent since the Peace Accords, so that 80 percent of rural households are now within six kilometers from a public telephone. Although real electricity tariffs increased by 60-80 percent following the reform, residential consumers have been shielded by a "social tariff" policy that has kept charges at pre-reform levels. This policy, which costs US$50 million a year, does little to benefit poor households. The reason is that 60 percent of poor households are not connected to the electricity network, and those that are consume modest amounts of electricity and hence capture only 10 percent of the total value of the subsidy. In contrast, poor households without access to electricity pay about US$11 a kilowatt-hour (or 80 times the electricity tariff) to light their homes with candles and wick lamps. The resources used to finance the "social tariff" would therefore be better used in further accelerating the pace of new connections for currently underserved households.